1986
DOI: 10.1159/000173093
|View full text |Cite
|
Sign up to set email alerts
|

Whole Kidney Response to Reduced Arterial Pressure during Converting Enzyme Inhibition in the Rat

Abstract: Autoregulatory efficiency of renal blood flow (RBF) and glomerular filtration rate (GFR) was evaluated in male Sprague-Dawley rats during interference with the renin-angiotensin system by a converting enzyme inhibitor (CEI), captopril (3 mg · h-1 · kg-1 BW). RBF and GFR were approximately 25 (p < 0.01) and 20% (p < 0.02) higher, respectively, in rats infused with CEI than in control rats at spontaneous renal arterial pressure (RAP). A reduction of RAP to 100 mm Hg (within the autoregulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…ANG II also did not affect renal medullary blood flow autoregulation (288). However, ANG II was more important in steadystate autoregulation of the GFR than the RBF (488,550,774,1261), especially at lower RPP, most likely by maintaining efferent arteriolar tone. However, a few studies have reported that the RAS was essential for effective steadystate autoregulation of RBF and GFR (764,1479).…”
Section: A Ang IImentioning
confidence: 90%
“…ANG II also did not affect renal medullary blood flow autoregulation (288). However, ANG II was more important in steadystate autoregulation of the GFR than the RBF (488,550,774,1261), especially at lower RPP, most likely by maintaining efferent arteriolar tone. However, a few studies have reported that the RAS was essential for effective steadystate autoregulation of RBF and GFR (764,1479).…”
Section: A Ang IImentioning
confidence: 90%
“…This apparent contradiction may, however, be an effect of a time-dependency of the mechanisms responsible for GFR regulation. Sjoquist & Goransson (1984) observed that SNGFR was efficiently autoregulated immediately after a reduction in RAP to 70 mmHg. A gradual decrease in SNGFR was seen when RAP remained lowered for 5 min or more.…”
Section: Discussionmentioning
confidence: 97%
“…The preparatory procedures have been described in detail earlier (Sjoquist & Goransson 1984). but will be summarized here.…”
Section: Preparationsmentioning
confidence: 99%
See 2 more Smart Citations